Survival and Determinants of Liquidation of Savings and Credit Cooperatives in Ecuador - Andrade Condor, Alexander (2024)
Ecuadorian Savings and Credit Cooperatives (COACs) are classified into five segments based on their asset level, with segment 1 having the highest level and segment 5 having the lowest. From 2014 to 2022, the share of COAC assets in the financial system increased from 18 % to 29 %. In 2022, there were 461 active COACs and 96 liquidated (98 % in segments 3, 4, and 5). In this context, a study was conducted to examine the liquidation of COACs through survival analysis and logistic regressions. The study used data from 456 cooperatives observed over 25 quarters between 2016 and 2022. The survival models indicate a survival probability of over 90 % throughout the period in segments 3 and 4, while the survival probability in segment 5 is around 60 %. In addition, the logistic regressions suggest that administrative management and coverage level are protective factors against liquidation, while the number of branches is associated with an increased risk factor.